ANALISIS PENYUSUNAN ANGGARAN DAN LAPORAN REALISASI ANGGARAN DANA BAGI HASIL MIGAS PADA DINAS PENDIDIKAN PROVINSI ACEH - Budi Safatul Anam; Aliamin Aliamin; Eva Zahara (KOLEGIAL, 2018)
This study aims to analyze the preparation and realization of the Aceh Education Office's budget sourced from Oil and Gas Revenue Sharing Funds (DBH) during the 2016-2017 fiscal year. This research is a qualitative research, with data analysis techniques using calculation of financial ratios to determine the level of budget realization. The results showed that the budgeting of the Aceh Education Office sourced from the Oil and Gas DBH was discussed and agreed upon between TAPA and the Aceh Education Office as SKPA in the Musrenbang held specifically for development programs / activities sourced from Oil and Gas DBH concurrently with Special Autonomy, facilitated by Aceh Bappeda. The realization of Oil and Gas DBH at the Aceh Education Office is still very lacking in 2016, but has begun to improve the following year. Judging from the implementation of the program, the decline in the realization of the 2016 budget was due to several programs that received funding priorities or obtained relatively large budget allocations which experienced very little realization, resulting in several activities that could not be optimally funded.